Situating partnership activity, an activity theory inspired analysis of school to school inquiry networks - Andrew Townsend (Cogent Education, 2019)
The issue of how schools work in partnership with each other and with other organisations has always been of interest to school leaders, policymakers, and practitioners. This article adds to the body of research on partnerships in part by focussing on school to school partnerships and in part through the use of activity theory as an analytical tool. This is based on a study which examined how school partnerships developed, and of what helped and hindered this process. Drawing from activity theory this article presents a “situated” concept of school partnerships emphasising “nested” (within the school) and “overlapping” (between school) features. The successful operation of any partnership, it is argued, requires consideration of both of these components of partnership, and of how they relate to one another.